Telemedicine technologies : information technologies in medicine and telehealth - Fong, Bernard (John Wiley & Sons, 2011)
This book brings together a broad range of topics demonstrating how information and wireless technologies can be used in healthcare. In this book, the authors focus on how medical information can be reliably transmitted through wireless communication networks. It explains how they can be optimized to carry medical information in various situations by utilizing readily available traditional wireless local area network (WLAN) and broadband wireless access (BWA) systems. In addition, the authors discuss consumer healthcare technology, which is becoming more popular as reduction in manufacturing c.